Exploring integrated methodology for phytoremediation and biofuel production potential of Eichhornia crassipes (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Eichhornia crassipes (EC) is a well-known invasive weed in different aquatic ecosystems. Its effective and complete eradication remains a challenge. The plant is a heavy metal (HM) hyperaccumulator in water bodies; however, studies regarding its biomass utilisation post-phytoremediation remain limited. The abundant growth rate and biochemical composition make EC a promising lignocellulosic feedstock for biofuel production; hence could be a deterministic approach for solving the twin problems of water pollution and higher energy demand, which are the global pressing issues in today’s scenario. The present study aimed at evaluating the phytoremediation potential of EC followed by proximate and biochemical analysis to investigate its suitability for biofuel production. After two weeks, the EC removed above 90% of Lead (Pb) and 60% of Cadmium (Cd) at all experimental doses. Lower doses of HMs, especially Pb, showed stimulatory effects on E. crassipes leaf biomass (ECLB). The recovered ECLB from Pb contaminated water (1 mg L−1) was further analysed for moisture (89.23±0.86%), dry matter (10.77±0.60%), ash (11.91±1.20%), organic carbon (51.56±1.08%), cellulose (21.89±0.64%), hemicellulose (26.50±1.13%), lignin (5.62±0.83%), total carbohydrate (32.00±1.58%), and protein (20.83±0.52%) content. SEM imaging of harvested ECLB confirmed compact and rigid structure. The recorded peaks in FTIR-spectra (1015.21, 1153.71, 1246.01, 1339.63, 1419.71, 1540.71, 1646.80, 1736.73, 2933.03, and 3263.72 cm−1) indicate the presence of lignocellulosic biomass. XRD peak at 21.55 confirmed the crystalline fraction of cellulose in ECLB. The results of theoretical yields of H2 and CH4 co-generation (HMG) (210.85 mLH2/g DW and 150.28 mL CH4/g DW) and Bioethanol (0.278 g/g DW) derived from cellulose and hemicellulose content of ECLB were comparable to those in reported studies. Overall, this work demonstrates an integrated methodology of phytoremediation followed by biofuel production from the recovered phytobiomass.